Takhrij and Syarah Hadith about Chemistry: Prohibition of Eating Petai Excessively in Science and Hadith - Annisaa Sufi Khanifah; Wahyudin Darmalaksana; Abdul Syukur; Tina Dewi Rosahdi (Gunung Djati Conference Series, 2021)
The purpose of this study was to discuss the hadith of the Prophet Muhammad about eating excessive petai. The qualitative research method uses the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study are the dangers arising from excessive petai consumption. The conclusion of this study is the takhrij and syarah hadith of the Prophet SAW regarding the excessive prohibition of the compounds it contains based on chemical analysis